Factors affecting the purchase intention of properties for investment in Klang Valley - Wong, Ka Fee (2019)
Due to the significant increase in the household debt ratio and the decline in the house -affordability index, Bank Negara Malaysia (BNM) introduced a series of cooling measures to curb the current property speculation activities in Malaysia. Under the context of cooling measures, investors’ purchase intention seems to remain unclear whereby consumers may react differently and perceive their attitudes and behaviours individually. The objective of this research was to examine the relationships between investors’ key determinants and the property purchase intention under the implementation of the government’s cooling measures. The independent variables included finance, attitude, subjective norms and perceived behaviour control, while the dependent variable was property purchase intention; and the moderator was financial knowledge. The Theories of Planned Behaviour and the Behavioural Finance Theory were adopted to support the research framework. The target population was Malaysian investors who had the intention to invest in properties and the sample population was Malaysian investors who had the intention to invest in properties located in the Klang Valley. In total, 450 questionnaires were distributed in the property showcases located in Klang Valley. Smart PLS 3.0 was adopted to analyze the results. Results of the study showed there were significant relationships between the independent variables (finance, attitude, subjective norms and perceived behaviour control) and property purchase intention. In addition, the hypotheses were also supported in that there was a significant moderating effect of financial knowledge on the relationship between the determinants (subjective norms and perceived behaviour control) and property purchase intention. However, the research found that financial knowledge did not moderate the relationship between attitude and purchase intention. The government and the intermediaries should take this research as a guide in understanding the problems and concerns of property investors and revising the regulations and rules with regards to property financing and development.